The Impact of Microdata in Norwegian Historiography 1970 to 2020 - Sommerseth, Hilde Leikny; Thorvaldsen, Gunnar (Historical Life Course Studies, 2022)
The establishment of the Norwegian Historical Data Centre, the 1801 project at the University of Bergen and the data transcriptions and scanned versions of the sources in the National Archives made Norwegian microdata much more available. A more detailed description of the digital techniques applied to the wealth of censuses, church records and other types of nominative data from the 18th century onwards, will be presented in a separate article. Our main focus here is to summarize the impact of the research that has been produced based on the Norwegian historical microdata. These studies span a wide range of fields within social history and historical demography: Emigration, immigration, internal migration, fertility, nuptiality, family history and last but not least mortality studies with a priority given to infant mortality. A recent development is the building of a national historical population register covering the 19th and 20th centuries.